Wave drag in front crawl swimming - Toussaint, H. M.; van Stralen, M.; Stevens, E. (ISBS - Conference Proceedings Archive (Konstanz), 2003)
When swimming at the surface, swimmers will experience wave drag. It is observed that above a certain speed, wave height grows rapidly with further speed increase, suggesting that wave drag cannot be neglected at high speed. Therefore, the magnitude of this component of total drag was estimated. Total drag was decomposed in 2 parts; wave- and pressure drag. Assuming wave drag to be negligible below 1.6 m•s-1, the velocity dependence of pressure drag was assessed by drag determinations at speeds below 1.6 m•s -1. By subtracting the estimated pressure drag from total drag values measured at higher speeds, wave drag was estimated. At a mean speed of 1.89 m•s -1, mean wave drag was 11.5 N, amounting to 12.1 % of total drag. These results underline the importance of reducing wave drag by diving under the surface after start and turns.